Philosophical Appraisal of Curriculum Design as Nigeria’s Educational Social Contract: A Systematic Review - Emmanuel Lucas Nwachukwu; Lasbrey Ikechukwu Unegbu; Godson Chidi Nwokorie; Sule Omeiza Adebayo (International Journal of Education, Culture, and Society, 2026)
Curriculum design in Nigeria is frequently treated as a technical or administrative activity, yet it also constitutes a central expression of the state’s commitments under its educational social contract. This systematic review examines whether Nigerian curriculum design fulfils the epistemic obligations embedded in that contract, using social contract theory as its analytical framework. A systematic search across seven academic databases was conducted, followed by PRISMA-guided screening. A total of 62 sources were analysed, comprising 40 core sources subjected to thematic synthesis and 22 sources used for theoretical and contextual framing. Five analytical themes emerged: the gap between policy declarations and curriculum realities; the persistence of colonial epistemological hierarchies; the epistemic consequences of current language policy; tensions between pedagogical ideals and transmission-oriented classroom practice; and the interdependence of curriculum, assessment, teacher education, and language reform. The findings indicate that Nigeria’s curriculum challenges extend beyond administrative implementation and reflect deeper philosophical questions concerning whose knowledge is legitimised, transmitted, and assessed through schooling. The review introduces epistemic obligation as a distinct dimension of state responsibility, arguing that curriculum reform must address epistemological justice rather than rely solely on policy revision. This study contributes to curriculum theory, decolonial education, and educational philosophy by reframing Nigerian curriculum design as a matter of epistemic accountability within the educational social contract, with implications for curriculum reconstruction, language policy, assessment reform, and teacher education.